UPAYA PERLINDUNGAN ANAK OLEH HAKIM DALAM PENETAPAN PERMOHONAN DISPENSASI NIKAH - Shoim; Yuni Roslaili (AHKAMUL USRAH: Jurnal S2 Hukum Keluarga dan Peradilan Islam, 2022)
Living as a child That must be carried out by the father accordingly with rule jurisprudence and law positivity. More mainly Again If has decided by the panel of judges own strength law. However in practice, the public still found neglect in living with children, as happened in Gampong Miruek Lamreudeup, District Baitussalam, Aceh Besar Regency. This study is about the implementation of living children post-divorce in the District Baitussalam, Aceh Besar Regency and for knowing effort law what can be done by a mother if there is no fulfillment of living children post-divorce.Study This includes a type of study field (field research), which is of the nature of juridical empirical. This study was carried out in Gampong Miruek Lamreudeup, District Baitussalam, Aceh Besar Regency. Research results can be mentioned 1. There are several forms: a. Party For fulfillment, a living child after divorce, just a mother from the child (ex wife) and assisted by parents from the party mother. Husband doesn't give a living to child because domiciled husband is not known by the wife; however, duly known husband fills the decision panel of judges. b. a livelihood child borne by the mother half a day and a half a day again by the ex husband (father). 2. Possible legal remedies done If there is no living child post-divorce, then the party mother can finish it through apparatus village local. If at level village no can be resolved, then party mother in the matter as the winning side can submit the lawsuit fulfillment obligation of giving the living maintenance child to Court Sharia. Furthermore Court Sharia will do execution in case living child. The Execution of the judge's decision has been made a powerful law, but it is still the final process in the civil or criminal case in court.